SANKSI ADAT TERHADAP PERKAWINAN SESUKU DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR BERDASARKAN HUKUM ADAT KAMPAR - Sandy, Ferri; Hanifah, Mardalena; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Marriage is a bond physically and mentally between a man and a woman as husband and wife with the aim of forming a family or household that is happy and eternally based on God. Not all marriages can take place, even though the marriage has met all the pillars and the conditions stipulated. As well as the ban on intermarriage indigenous tribe at the Tanjung Village, Subdistrict Koto Kampar Hulu, Kampar District. A ban on marriage is that tribal customs rules that have long been in force. This is because the community is adopting exogamy in which a man or woman is required to marry with people outside the family clan. The problem of this essay, namely: First, What are the factors causing the banning marriage tribesmen at the Tanjung Village Subdistrict Koto Kampar Hulu Kampar District? Second, whether the sanction against the perpetrators of marriage tribesmen at the Tanjung Village Subdistrict Koto Kampar Hulu Kampar District? Third, How does the process of applying sanctions against the perpetrators of customary marriages tribesmen at the Tanjung Village Subdistrict Koto Kampar Hulu Kampar District? This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Tanjung Village, Subdistrict Koto Kampar Hulu, Kampar District, while the sample population is an all parties associated with the issues examined in this study, the data source used, primary data and secondary data, data collection techniques in this study with interviews and literature study. From the research, there are three things that can be inferred First, factors which led to the ban on marriage for their tribe is blood relation, will give birth to offspring quality, socially narrow, could decide the kinship, and will break the line. Second, the sanctions imposed against the perpetrators of that tribal marriage was fined a buffalo, expelled from their homes and should no longer re- settled in villages as husband and wife. Third, the process of implementation of sanctions against the perpetrators of indigenous tribesmen marriages conducted in the form of consultation or village meeting, attended by all Ninik Mamak , theologian and village authorities. Keywords : Indigenous Sanctions - Marriage Tribesmen - Tanjung Village